The Arabo-Tiberian Vocalisation System: An Undocumented Set of Medieval Vowel Signs for the Hebrew Script - Posegay, Nick (Folia Orientalia, 2025)
The three main Hebrew vocalisation systems—Tiberian, Palestinian, and Babylonian—are well-known in the history of Semitic languages. This article describes another previously undocumented Hebrew vocalisation system, the ‘Arabo-Tiberian system’, a sub-variant of the Tiberian system that appears only in Judaeo-Arabic manuscripts around the tenthand eleventh centuries. In addition to the typical Tiberian vowel marks, the Arabo-Tiberian system includes two loaned Babylonian signs, one for the vowel /u/ and another for /a/ (primarily in the diphthongs /aw/ and /ay/). This system never achieved the widespread adoption or standardisation of other Hebrew and Arabic vowel systems, so it survives now only in fragmentary evidence from the Cairo Genizah. This article describes the common Arabo-Tiberian features in ten vocalised manuscripts and offers hypotheses for the system’s origin and extinction.